Dissemination of virulence and resistance genes among Klebsiella pneumoniae via outer membrane vesicle: An important plasmid transfer mechanism to promote the emergence of carbapenem‐resistant hypervirulent Klebsiella pneumoniae. Issue 5 (25th June 2022) - Wang, Zhongxing; Wen, Zhe; Jiang, Min; Xia, Fufang; Wang, Min; Zhuge, Xiangkai; Dai, Jianjun
Abstract: Klebsiella pneumoniae is well‐known opportunistic enterobacteria involved in complex clinical infections in humans and animals. The domestic animals might be a source of the multidrug‐resistant virulent K. pneumoniae to humans. K. pneumoniae infections in domestic animals are considered as an emergent global concern. The horizontal gene transfer plays essential roles in bacterial genome evolution by spread of virulence and resistance determinants. However, the virulence genes can be transferred horizontally via K. pneumoniae‐ derived outer membrane vesicles (OMVs) remains to be unreported. In this study, we performed complete genome sequencing of two K. pneumoniae HvK2115 and CRK3022 with hypervirulent or carbapenem‐resistant traits. OMVs from K. pneumoniae HvK2115 and CRK3022 were purified and observed. The carriage of virulence or resistance genes in K. pneumoniae OMVs was identified. The influence of OMVs on the horizontal transfer of virulence‐related or drug‐resistant plasmids among K. pneumoniae strains was evaluated thoroughly. The plasmid transfer to recipient bacteria through OMVs was identified by polymerase chain reaction, pulsed field gel electrophoresis and Southern blot. This study revealed that OMVs could mediate the intraspecific and interspecific horizontal transfer of the virulence plasmid phvK2115. OMVs could simultaneously transfer two resistance plasmids into K. pneumoniae and Escherichia coli recipient strains. OMVs‐mediated horizontal transfer of virulence plasmid phvK2115 could significantly enhance the pathogenicity of human carbapenem‐resistant K. pneumoniae CRK3022. The CRK3022 acquired the virulence plasmid phvK2115 could become a CR‐hvKp strain. It was critically important that OMVs‐mediated horizontal transfer of phvK2115 lead to the coexistence of virulence and carbapenem‐resistance genes in K. pneumoniae, resulting in the emerging of carbapenem‐resistant hypervirulent K. pneumoniae .